Alta proporción de macrodisco en pacientes de dos centros oftalmológicos en el occidente de Honduras - Astrid Mariam Enamorado Ortega; Diana Sofía Pérez Osorio; Allan Daniel Hernández Briceño; Carolina Rodríguez Libreros (Revista Médica Hondureña, 2023)
Background: When the optic nerve has a surface greater than 2.5mm2, and without associated pathologies, it is a macrodisc, whose excavation is proportional to its increased size. Based on the distribution under the Gauss curve, it can be defined as a “macrodisc” when it is more than 2 standard deviations above the mean. Only 2.3% of the population is expected to exceed these limits. Objective: To determine the average optic disc size and the proportion of macrodisc in the population without glaucoma or retinal pathologies that attends two ophthalmological clinics in Western Honduras in the period from July 2021 to July 2022. Methods: Retrospective descriptive study. Morphometric parame-ters of the optic disc were measured using ZEISS Cirrus HD Model 4000 Optical Coherence Tomography. Macrodisc was defined as: optic disc area >2.5 mm2 and disc area of the mean plus twofold standard deviations. Results: The proportion of macrodisc was 31% considering the definition of disc area >2.5 mm2, and 3% con-sidering the definition based on the distribution under the Gauss curve (>3.17mm2). An average optic disc area of 2.28±0.45 mm2was obtained, cup/disc (C/D) ratio of 0.59±0.13, vertical C/D ratio of 0.56±0.13, neuroretinal rim area of 1.37±0.22 mm2, retinal nerve fiber layer thickness (CFNR) of 97.4±10.664μm. Discussion:The average disc area obtained is greater than Caucasians, like Hispanics, and less than Afro-descendants and Asians.